Evolution in optical molecular imaging techniques guided nerve imaging from 2009 to 2023: a bibliometric and visualization analysis - Wenkai Liang; Yan Liu; Erlong Jia; Xiaofeng Yang; Shufeng Han; Jinzheng Wei; Jinzheng Wei; Wei Zhao (Frontiers in Neurology)
BackgroundRecent years, the use of optical molecular imaging (OMI) techniques guided nerve imaging has made significant progress. However, a comprehensive bibliometric analysis in this field is currently lacking. In this study, we aim to shed light on the current status, identify the emerging hot topics, and provide valuable insights for researchers within this field.MethodsIn this study, we collected 414 research via the Web of Science Core Collection (WoSCC) from 2009 to 2023. CiteSpace, VOSviewer and R package “bibliometrix” were used for analysis of countries, institutions, journals, etc., to evaluate the trends.ResultsThe amounts of publications in relation to OMI guided nerve imaging has been increasing. United States and China contributed to over 60% of the publications. The Shanghai Jiao Tong University contributed the highest number of publications. Investigative Ophthalmology and Visual Science is considered the most prestigious and prolific journal in the field. It is also widely regarded as the most cited journal. Among the top 10 authors in terms of output, Hehir CAT has the highest number of citations. The “neurosciences neurology,” “science technology other topics,” and “ophthalmology” are representative research areas. The main cluster of keywords in this field includes “axonal regeneration,” “mouse,” and “optical coherence tomography.”ConclusionThis bibliometric investigation offers a comprehensive portrayal of the structure of knowledge and the progression patterns, presents an all-encompassing synthesis of findings, discerns and illustrates the forefront within OMI guided nerve imaging for the first time. It will provide a valuable reference for relevant scholars.